تقييم واقع الموارد والاحتياجات المائية لحوض الفرات - محمود يوسف; عطية قصي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعتبر حوض الفرات من أهم الأحواض المائية السورية على الإطلاق باعتبار المصدر الرئيسي لمياهه هو نهر الفرات الذي يأتي في مقدمة الموارد المائية السورية أهمية. يقع حوض الفرات في الشمال الشرقي من سورية وضمن محافظات حلب - الرقة -دير الزور- الحسكة - حمص. ويأتي في الدرجة الثانية من حيث المساحة بعد حوض البادية. وفي دراستنا لواقع الموارد والاحتياجات المائية لحوض الفرات تم تخصيص أربعة جوانب رئيسية للدراسة . الجانب الأول تناول واقع الموارد المائية للحوض. وأما الجانب الثاني كان حول الاستخدامات المائية لمنطقة الحوض . وفي الجانب الثالث قمنا بتبيان الميزان المائي في ضوء بيانات الموارد والاحتياجات المائية للحوض . الجانب الرابع تم دراسة آليات الاستثمار الأمثل لمياه حوض الفرات من خلال استعراض مشاريع استصلاح الأراضي المتعاقبة والمستقبلية المتوقعة، إضافة إلى تطوير أساليب وأنظمة الري في الحوض بما يضمن الحد من الهدر والفاقد والتلوث وتحسين نوعية المياه . وتم دراسة إمكانية تأمين حصة عادلة ومعقولة من مياه نهر الفرات لسورية. وقد توصلنا من خلال دراسة سبل وآليات استثمار مياه الفرات بالشكل الأمثل، وخصوصاً الإست خدامات الزراعية إلى رفع فائض الميزان المائي للحوض من 97 م.م3 إلى 4, 1512 م.م3. Euphrates basin considers as the most important Syrian basin because the major resource of water in Syria is Euphrates river which it is the first Syrian water resource . Euphrates basin is East north Syria in few countries: Halab, Raqa, Der al Zor, Al Hasaka, homs. It is the second in area after Badia basin. In our study of the reality of resources and the water needs of the basin of the Euphrates was the allocation of four key aspects of the study. The first dealt with the reality of water resources of the basin. Omaganb and the second was about the uses of water to the pelvic area. In the third aspect by showing we have the water balance in the light of data resources and water needs of the basin. The fourth side was the best investment study of the mechanisms of water from the Euphrates basin during the review of successive land reclamation projects and the expected future, as well as to develop methods and systems of irrigation in the basin to ensure the reduction of waste and waste and pollution and improve water quality. Was studying the possibility of securing a fair and reasonable share of water from the Euphrates to Syria. We have reached through the study of ways and investment mechanisms to optimize the water of the Euphrates, and especially agricultural uses to raise the water balance of the basin of 97 m. M 3 to 4.1512 m. M 3...